2016
DOI: 10.1038/cddis.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Activation of salt-inducible kinase 2 promotes the viability of peritoneal mesothelial cells exposed to stress of peritoneal dialysis

Abstract: Maintaining mesothelial cell viability is critical to long-term successful peritoneal dialysis (PD) treatment. To clarify the viability mechanism of peritoneal mesothelial cells under PD solutions exposure, we examined the mechanisms of cellular response to this stress conditions. Here we report that the proteasome activity is inhibited when treated with PD solutions. Proteasome inhibition-mediated activation of salt-inducible kinase 2 (SIK2), an endoplasmic reticulum-resident protein, is important for mesothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The activation of Beclin 1-dependent autophagy results in decreases of the viability of peritoneal mesothelium cells and finally PD failure [105]. Another study, however, suggests that the PD solution promotes autophagosome formation and decreases cells death to maintain the PD function [106]. Therefore, future studies are required to understand the exact relationship of dialysis and autophagy regulation.…”
Section: Autophagy In Dialysis and Renal Transplantationmentioning
confidence: 99%
“…The activation of Beclin 1-dependent autophagy results in decreases of the viability of peritoneal mesothelium cells and finally PD failure [105]. Another study, however, suggests that the PD solution promotes autophagosome formation and decreases cells death to maintain the PD function [106]. Therefore, future studies are required to understand the exact relationship of dialysis and autophagy regulation.…”
Section: Autophagy In Dialysis and Renal Transplantationmentioning
confidence: 99%
“…In patients undergoing PD treatment, the mesothelial cells exposed to PD solution showed a significant activation of the autophagy and inhibition of proteasome activity to maintain the viability of mesothelial cells during renal replacement therapy. 39 Contrarily, another study reported that autophagy promoted epithelial to mesenchymal transition, fibrosis, and apoptosis in human peritoneal mesothelial cells. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Sik2 is highly enriched in interscapular BAT. Phosphorylation of SIK2 at Thr175/Thr163 is the hallmark of its kinase activation 38,39 . However, the role of HS in lipid metabolism and fat deposition is debated.…”
Section: Discussionmentioning
confidence: 99%